Pasola Culture Seen from the Uniqueness of Its Implementation According to the Districts of Wanokaka and Lamboya: An Ethnographic Perspective - Erlinyanti Ristina Lende; Mikael Samin; Andrinata Andrinata (Journal of Social and Humanities, 2025)
This study aims to examine the uniqueness of Pasola cultural practices in both districts, identify the similarities and differences from geographical and cultural perspectives, and explore the cultural values that can be utilized as learning resources in cultural geography. The research employed a qualitative method with an ethnographic approach. Data were collected through participatory observation, in-depth interviews with traditional leaders (Rato), Pasola participants, local communities, and field documentation. Data analysis was conducted through reduction, presentation, and verification to obtain a comprehensive understanding of Pasola practices. The findings reveal that Pasola in Wanokaka and Lamboya Districts shares similarities in ritual functions, the symbolism of blood as fertility, and the central role of the Rato as the spiritual leader. However, differences are found in the timing of the event, the arena setting, community participation, and the ritual atmosphere. Pasola in Wanokaka is more sacred, held in coastal areas, and closely tied to the emergence of nyale (sea worms), while in Lamboya it is more open, inclusive, and celebrated as a lively social festival in the highlands. The cultural values embedded in Pasola include religiosity, togetherness, discipline, leadership, and resilience. These values have great potential to be applied as cultural geography learning resources, as they reflect human-environment interactions, community attachment to place, and the role of tradition in strengthening local identity. This research is expected to contribute to the preservation of local culture and serve as a reference for developing geography learning based on local wisdom and cultural tourism in West Sumba Regency.